Matemática elemental para estudiantes universitarios - Aro, Alex; Santander, Oscar (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is designed for undergraduate students who are starting their professional training in public and private universities; the content of the book is equivalent to the basic mathematics course, which corresponds to general studies that are taught in different professional schools, an important characteristic of this book. The book "Elementary Mathematics for university students" is a collection of solved and proposed exercises, which will directly contribute to developing their abilities and skills in solving exercises and problems. This book tries to complement the previous knowledge acquired at the secondary level and, simultaneously, deepen the topics with a compact and concise approach starting with the basic level and gradually developing up to the advanced level of mathematics that is fundamental in fields related to mathematics. engineering, biomedical and social. Our main objective is to cover all the necessary mathematics topics so that in the future, the student is in a position to face courses such as differential and integral calculus, vector calculus, differential equations, and others. During the last five years, the authors regularly taught the basic mathematics course and advanced courses in different professional schools of the National University of the Altiplano, the written notes that are presented began to materialize in the semesters 2021 - II and 2022 - I, considering the Valuable opinions and comments from students and colleagues who have greatly influenced the preparation and organization of the book’s content. We are very grateful to our students and colleagues for their valuable input, and we look forward to receiving any comments or suggestions for future editions.